PHYTOCHEMICAL INVESTIGATION OF LEAVES AND SEEDS OF CORCHORUS OLITORIUS L. CULTIVATED IN IRAQ - Hasan, Hayder T; J Kadhim, Enas (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to investigate chemical constituents of leaves and seeds of Corchorus olitorius since no phytochemical investigation had been done previously in Iraq. Methods: Leaves and seeds of C. olitorius were defatted by maceration in hexane for 24 h. The defatted plant materials were extracted using Soxhlet apparatus, the aqueous methanol 85% as a solvent extraction for 24 h, and fractionated by petroleum ether, chloroform, ethyl acetate, and n-butanol. The ethyl acetate, n-butanol, and n-butanol after hydrolysis fractions for each part (leaves and seeds) were analyzed by high-performance liquid chromatography (HPLC) and high-performance thin-layer chromatography (HPTLC) for its phenolic acid and flavonoid contents. The petroleum ether fraction from the leaves was analyzed using Gas chromatography/mass spectrometer (GC/MS). Flavonoids and phenolic acid derivative were isolated from the ethyl acetate of leaf fraction and n-butanol after hydrolysis fraction of the seeds and identified by mass spectrometry, infrared, HPLC, and HPTLC. Results: The different chromatographic and spectroscopic results revealed the presence of luteolin, quercetin, astragalin, isoquercetin, catechins, and 3,5-dicaffeoylquinic acid (3,5-DCQA) in both leaves and seeds of C. olitorius and also 17-octadecynoic acid, 9-octadecanoic acid (oleic acid), hexadecenoic acid (palmitic acid), 9,12-octadecanoic acid (linoleic acid), octadecadien-1-ol (Î²-sitosterol), and Î±-tocopherol (Vitamin E) in the petroleum ether fraction of C. olitorius leaves. Conclusion: The results of the current study proved the presence of 3,5-DCQA, astragalin, and isoquercetin in the ethyl acetate fraction of C. olitorius leaves and catechin in the n-butanol after hydrolysis fraction of C. olitorius seeds. Â 